2020
DOI: 10.1016/j.eucr.2019.101018
|View full text |Cite
|
Sign up to set email alerts
|

Benign renal schwannoma: Case report and literature review

Abstract: Renal schwannoma is a very infrequent tumor. It is usually benign and it does not have any specific symptoms or imaging characteristics. Its final diagnosis is usually made after surgery. We present a 66 year-old-man that was referred to our center after the casual finding of a renal mass. With a suspected diagnosis of a renal cell carcinoma, a partial nephrectomy was performed. The histological study revealed the final diagnosis of a benign renal schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The first case was documented in 1955, and since then existing literature reviews have identified approximately 34 cases [6]. However, recent reports documenting renal schwannoma cases present varying, inconsistent statistics that may not accurately reflect the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first case was documented in 1955, and since then existing literature reviews have identified approximately 34 cases [6]. However, recent reports documenting renal schwannoma cases present varying, inconsistent statistics that may not accurately reflect the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…While retroperitoneal involvement is uncommon, renal schwannomas are extremely rare, with very few cases documented in the literature [ 4 ]. The first case was documented in 1955, and since then existing literature reviews have identified approximately 34 cases [ 6 ]. However, recent reports documenting renal schwannoma cases present varying, inconsistent statistics that may not accurately reflect the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients vary in age at diagnosis (14–89 years) with a median in the 5th decade of life, and additionally a female predominance. 2 , 3 …”
Section: Discussionmentioning
confidence: 99%